2019
DOI: 10.1016/j.jmarsys.2019.103190
|View full text |Cite
|
Sign up to set email alerts
|

Eastern Mediterranean salinification observed in satellite salinity from SMAP mission

Abstract: One of the saltiest seas, the Mediterranean, experiences significant salinity variations in near surface layers. Satellite sea surface salinity (SSS) data obtained using Soil Moisture Active Passive (SMAP) mission indicate steady salinification of the eastern Mediterranean Levantine Basin at a rate of ~0.14 psu/year during 2015-2018. Satellite-observed salinity changes are confirmed by Argo float data and suggest possible changes in properties of the Levantine Intermediate Water. Eastern Mediterranean salinifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Several studies reported that SMAP is able to retrieve SSS with some confidence in coastal regions within 500-1000 km offshore in many places around the globe [11][12][13][14][15][16][17][18][19]. The present study adds another region to that list: the Red Sea.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Several studies reported that SMAP is able to retrieve SSS with some confidence in coastal regions within 500-1000 km offshore in many places around the globe [11][12][13][14][15][16][17][18][19]. The present study adds another region to that list: the Red Sea.…”
Section: Discussionmentioning
confidence: 78%
“…In the Mediterranean Sea, bias is positive for the TSG and negative for Argo [3], but that was for a previous SMAP version than the ones used here. Moreover, there is no outstanding offset in Figure 14, such as in the Levantine area of the Mediterranean Sea (Figure 3a of Tang et al [17]).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Several studies have already proved that SMAP performs better within 500–1,000 km of coastal regions at several places around the world (Fournier et al., 2016, 2017; Grodsky et al., 2018, 2019; Lee et al., 2019; Vazquez‐Cuervo et al., 2018, 2019). For instance, Fournier et al.…”
Section: Resultsmentioning
confidence: 99%